Automatic data gathering dan processing software solution for industrial deformation analysis - M. Idris, Khairulnizam; Setan, Halim (2007)
Robotic Total Station or Robotic Tachometry System (RTS) widely used for surveying purpose and solution. From surveyor to archeologist, professional used RTS to solve many problems in collecting data such as to mapping the land use, archeology excavation site or used in construction field. Latest technology adopted in modern total station is servo motors to drive both the horizontal and vertical motion of the instruments. This technology is designed specially to search automatically for prism target known as Automatic Target Recognition (ATR). Manufacturers such as Leica Geosystem, TOPCON Instrument, Trimble and Geodimeter have designed an instrument with automatic target recognition (ATR). Usually, RTS will be used in precise measurement application such as deformation monitoring or dimensional surveying for industrial applications. Both applications needed high precision and accuracy instrument and also robust data analysis. This paper describes and discusses about industrial deformation software known as InDA (Industrial Deformation Analysis Software). The discussion include from the development process and then the testing of the software. The data gathered from InDAS are compared with other instrumentation, measurement technique and commercial software.